Dimension Reduction for Computational Enhancements in Thin Film Electrochemical Modelling. Issue 14 (1st January 2016) - Simillion, Hans; Van den Steen, Nils; Montoya, Rodrigo; Terryn, Herman; Deconinck, Johan
Abstract : The application of mechanistic electrochemical models is limited to small scale or short term simulations because of the high computational cost. In this work a model is developed to decrease the computational time by applying a dimension reduction based on an averaging theorem. In an example, a two-dimensional problem is reduced to a subsystem of coupled one-dimensional problems. For thin electrolyte films, the deviation between the two models becomes negligible; at an electrolyte thickness of 5% of the electrode width, the underestimation error drops below 10%. We can conclude that the dimension reduction is appropriate when dealing with thin electrolyte layers such as in atmospheric corrosion.